Flow cytometric assay for quantifying opsonophagocytosis and killing of Staphylococcus aureus by peripheral blood leukocytes. - Martin, E (1992)
We describe a novel flow cytometric method for quantifying opsonophagocytosis and killing of Staphylococcus aureus in cell-rich plasma obtained after dextran sedimentation of erythrocytes. To analyze opsonophagocytosis, phagocytes were labeled with a phycoerythrin-conjugated monoclonal antibody and were incubated with viable staphylococci containing carboxyfluorescein as a vital fluorescent dye. Phagocytosing cells assumed a dual, orange-green fluorescence. The relative numbers of bacteria associating with phagocytes could be determined by quantifying the decrease of free green fluorescent particles. A parallel incubation of fluorescent bacteria with unlabeled cell-rich plasma was performed to assess phagocytic killing. Blood cells were lysed with 3-[(3-cholamidopropyl)-dimethyl-ammonio]-1-propanesulfonate. This detergent spared viable bacteria, and residual green fluorescent particles were counted. The decrease in the number of these particles relative to the controls yielded the degree of killing. At bacteria-to-phagocyte ratios of 1:1 and 10:1, approximately 36 and 75% of the phagocytes participated in opsonophagocytosis, respectively. Over 90% of the staphylococci were phagocyte associated after 30 to 60 min. Killing rates were on the order of 66% +/- 12% and 80% +/- 7% after 1 and 2 h of incubation, respectively. These numbers, which were confirmed by colony countings, were significantly lower than those reported in the majority of past reports.